Failed diagnostic hysteroscopy: Analysis of 62 cases. (February 2020) - Genovese, Fortunato; D'Urso, Gisella; Di Guardo, Federica; Insalaco, Giulio; Tuscano, Attlio; Ciotta, Lilliana; Carbonaro, Antonio; Leanza, Vito; Palumbo, Marco
Abstract: Objective: The aim of the presented study is to improve the office hysteroscopy success rate identifying some of the factors associated to an unsuccessful procedure. Moreover it would highlight the importance of an adequate patients follow up after office hysteroscopy failure enlightening the uterine pathologies missed at the first attempt. Studydesign: This is a retrospective observational study. The Authors reviewed the medical records related to 516 office hysteroscopies performed from January 2016 to November 2018, extrapolating the data from the failed hysteroscopies occurred during this period. After the procedure failure all patients were offered to repeat the hysteroscopy under regional anesthesia in order to identify and treat uterine pathologies. Those patients, who declined to repeat the procedure, received an appropriate follow up. Each failure case is correlated with patient clinical characteristics, indications to hysteroscopy, risk factors presence, hysteroscopy patient compliance, pathology result and patient follow up. Results: The presented study shows an office hysteroscopy failure rate of about 12 %. Severe pain due to cervical stenosis, previous uterine surgery, postmenopausal status and marked uterine ventrifixation/retroflexion, represent the main reason why the procedure was not completed in an office setting. The uterine cavity was subsequently examined in only 26 (42 %) out of 62 patients who reported hysteroscopy failure, mostly repeating the procedure under regional anesthesia (24 cases) or performing vaginal hysterectomy for associated benign gynaecological pathology (2 cases). Endometrial malign pathology (endometrioid carcinoma) was diagnosed in 2 cases of them (7.7 %). Moreover the endometrial cavity remained so far unexplored in 36 (58 %) out of 62 patients, due to the patient refuse to repeat the hysteroscopy under anesthesia. Discussion and conclusion: Results of the present study suggest that office hysteroscopy should be sussessful at the first attempt due to the patients' refuse, in majority of cases, to repeat the procedure after a failure. To not repeat the hysteroscopy may lead to lose or delay important diagnosis, such as that of endometrial cancer. In this context, to counsel all patients prior the procedure may singnificanly help to identify those who may benefit of pharmacological cervical softening, local anesthetic injection or small caliber hysteroscopes usage, increasing the procedure success rate.